Distribution of Bamboo under the Edaphic and Climatic Conditions of Bangladesh - Hassan, M. M.; Alam, M. K.; Mazumder, A. H. (Indian Forester, 1988)
The relationship of the distribution of various bamboo species in Bangladesh and their edapbic and climatic variations has been discussed in this paper.